Pemanfaatan Limbah Koran Bekas Menjadi Kerajinan Di Lingkungan Sekitar Desa Ngesrepbalong - Deraya, Reanita Anggis; Nuraeni, Mila; Selviana, Sinta (PT.Mantaya Idea Batara, 2023)
The focus of this dedication activity is training in household garbage management, especially used newspapers, and the handmade manufacture of such papers because many used papers are piling up and confused citizens must be eaten instead of burned. To that goal, on 15 July, it used a community-based participatory methodology through planning, implementation, and evaluation phases. There were 15 participants, children and teenagers, sons and daughters of the village of Ngrepbalong, Kendal district, Limbangan district. About 80% of participants understood the socialization of used paper garbage management and training to make crafts like pencil connectors and photo frames. It shows a positive response because they understand the training given. Therefore, it is hoped that this activity will raise the awareness of the village community in the wise management of garbage and the use of recyclable waste for economic benefits.